Problems and Solutions of Pharmaceutical Packaging in Bulk - R. Yu. Garankina; V. V. Ryazhenov; E. A. Maksimkina; V. S. Fisenko; A. V. Alekhin; V. V. Tarasov; K. A. Chizhov; I. F. Samoshchenkova; N. Yu. Behorashvili; E. R. Zakharochkina (Фармация и фармакология (Пятигорск))
To date, pharmaceutical activities in the manufacture of medicines in a pharmacy, intra-pharmacy packaging of registered medicines in Russia and the countries of the Eurasian Economic Union (EAEU), is one of the priorities of regulatory authorities in order to improve drug supply.The aim. To study the current state of legal regulation of the circulation of medicines “in bulk” and the possibility of their packaging in a pharmacy.Materials and methods. To solve the tasks set, the methodology of system analysis in the field of drug provision, content analysis of documents regulating the sphere of circulation of drugs was used. The regulatory framework of the study was the legislative and by-laws regulating the sphere of circulation of medicines of the Russian Federation and the common market of the EAEU. The search for regulatory legal acts was carried out in the Directory of the legal system “ConsultantPlus”. In the course of the research, a set of scientific methods was used such a systematic, logical, structural and comparative.Results. The article consider the issues of legal regulation of the circulation of medicines “in bulk” in the pharmaceutical market. The current state of the legislative and regulatory framework has been studied and the problems of legal regulation of packaging of medicicnes “in bulk” in pharmacies have been identified. The article also focuses on the general problem of compliance with modern packaging requirements for medicines compounded in pharmacy. The possibility of introducing a new concept of “Pharmacy packaging” into Federal Law No. 61-FZ dated April 12, 2010 “On the circulation of medicines” is considered. The approaches developed in world practice to the regulation of issues related to the packaging of drugs “in bulk” in pharmacy are considered. Based on the results of the study, the possibilities have been identified and ways to improve the mechanisms of state regulation have been proposed.Conclusion. Packaging of medicines “in bulk” will increase the effectiveness of individual drug therapy, optimize and reduce the cost of circulation of budget funds, pharmacies and citizens.